2004
DOI: 10.1016/j.bbamcr.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

S100B-stimulated NO production by BV-2 microglia is independent of RAGE transducing activity but dependent on RAGE extracellular domain

Abstract: The Ca(2+)-modulated protein, S100B, is expressed in high abundance in and released by astrocytes. At the low levels normally found in the brain, extracellular S100B acts as a trophic factor, protecting neurons against oxidative stress and stimulating neurite outgrowth through its binding to the receptor for advanced glycation end products (RAGE). However, upon accumulation in the brain extracellular space, S100B might be detrimental to neurons. At relatively high concentrations, S100B stimulates NO release by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 36 publications
4
90
1
1
Order By: Relevance
“…Previous studies using primary microglia from newborn rat cortex or BV-2 microglial cell lines have demonstrated that micromolar to nanomolar concentrations of S100B cause IFNγ-induced expression of iNOS as well as NO secretion. 10,36 In contrast, our studies using BV2 and primary microglial cultures stimulated by LPS and/or IFNγ showed no effects of S100B on key markers of microglial activation, such as NO release or ROS production. Furthermore, it has been proposed that S100B may act through AGER and subsequently Toll-like receptors to induce inflammatory responses.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Icontrasting
confidence: 69%
See 2 more Smart Citations
“…Previous studies using primary microglia from newborn rat cortex or BV-2 microglial cell lines have demonstrated that micromolar to nanomolar concentrations of S100B cause IFNγ-induced expression of iNOS as well as NO secretion. 10,36 In contrast, our studies using BV2 and primary microglial cultures stimulated by LPS and/or IFNγ showed no effects of S100B on key markers of microglial activation, such as NO release or ROS production. Furthermore, it has been proposed that S100B may act through AGER and subsequently Toll-like receptors to induce inflammatory responses.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Icontrasting
confidence: 69%
“…The AGER-transducing activity may not have a significant role in S100B-stimulated NO production by microglia, but the AGER extracellular domain may be important for concentrating S100B on the BV-2 cell surface. 36 Studies have demonstrated that S100B-stimulated NO release from the microglia may be dependent on the density of AGER molecules on microglial surface and activation of pathways such as p38 MAPK (mitogen-activated protein kinase) that result in production of ROS. 36 Extracellular S100B can promote AGERdependent AP1 and nuclear factor (NF)-kB-dependent gene transcription of cytokines, chemokines, and iNOS, as well as AGER-independent NO production in microglia.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Imentioning
confidence: 99%
See 1 more Smart Citation
“…Primary microglia were isolated from 6-day-old CD rat (Charles River), WT C57BL/6 (Charles River) mouse, and Rage Ϫ/Ϫ mouse brain and characterized and cultivated as described (44). BV-2 microglia stably transfected with human RAGE cDNA (BV-2/RAGE microglia), human RAGE⌬cyto cDNA (BV-2/RAGE⌬cyto microglia), or empty vector (BV-2/mock microglia) were obtained as described (45). RAGE⌬cyto is a RAGE mutant lacking the cytoplasmic and transducing domain (46,47).…”
Section: Methodsmentioning
confidence: 99%
“…RAGE⌬cyto is a RAGE mutant lacking the cytoplasmic and transducing domain (46,47). BV-2 microglia express RAGE (45,46), and BV-2/RAGE microglia express larger amounts of the receptor compared with WT BV-2 microglia, whereas BV-2/RAGE⌬cyto microglia express endogenous RAGE plus the signaling-deficient RAGE mutant, RAGE⌬cyto (45). BV-2/mock, BV-2/RAGE, and BV-2/ RAGE⌬cyto microglia were cultivated as above except that gentamicin (5 g/ml) was used instead of penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%